Assessing Strength Effort in Pre-Adolescent Girls: Insights into Effort Accuracy at Different Strength Thresholds - Prashant Kumar Choudhary; Suchishrava Dubey; Bindiya Rawat; Sonu Kumar; Bhanu Pratap; Deepak Bangari; Sandeep Kumar; Sambhu Prasad; Dalveer Singh Kaunteya (OVS LLC, 2024)
Objectives. This study aimed to examine the peculiarities of strength effort assessment in girls aged 10, 11, and 12 years. Specifically, it sought to understand how these age groups evaluate effort at different percentages of their maximum strength (1/3, 1/2, and 2/3). Materials and methods. The study involved 75 girls divided into three age groups: 10 years (n = 20), 11 years (n = 25), and 12 years (n = 30). Participants' maximum hand strength was measured using a dynamometer, and their ability to assess effort at 1/3, 1/2, and 2/3 of this maximum was recorded. Results. The error of effort assessment was calculated and analyzed using paired and independent samples t-tests. Statistical significance was set at α = 0.05. The analysis revealed no significant age-related differences in hand maximum strength or strength effort assessment among the different age groups. The most accurate assessment of effort occurred at 2/3 of maximum strength for all age groups. Significant differences were found in effort assessment between 1/3 and 1/2 of maximum strength, and between 1/3 and 2/3 of maximum strength, with improvements noted as the effort percentage increased. However, no significant differences were observed between effort levels at 1/2 and 2/3 of maximum strength. Conclusions. The study indicates that the ability to assess strength effort remains stable across the age range of 10 to 12 years, with the most precise assessment occurring at 2/3 of maximum strength. The findings suggest that while overall strength assessment abilities are consistent, targeted training may enhance precision at different effort levels. This contributes to the understanding of motor function development and highlights the need for interventions to improve effort assessment skills in young girls.